Primary Investigation on Equivalent Anchoring Method of Jointed Rock Mass Tunnel and Its Engineering Application - Min Gao; Shanpo Jia (Advances in Civil Engineering)
Rock bolts, one of the main support structures of the tunnel, can improve the stress state and mechanical properties of the surrounding rocks. The rock bolts are simulated by bar or beam elements in present numerical calculations for most 2D tunnel models. However, the methods of simulating rock bolt in three-dimensional models are rarely studied. Moreover, there are too many rock bolts in the long-span tunnel, which are hardly applied in the 3D numerical model. Therefore, an equivalent anchoring method for bolted rock masses needs to be further investigated. First, the jointed material model is modified to simulate the anisotropic properties of surrounding rock masses. Then, based on the theoretical analysis of rock bolts in reinforcing mechanical properties of the surrounding rock masses, the equivalent anchoring method of the jointed rock mass tunnel is numerically studied. The equivalent anchoring method is applied to the stability analysis of a diversion tunnel in Western China. From the calculation results, it could be found that the reinforcement effect of rock bolts could be equivalently simulated by increasing the mechanical parameter value of surrounding rocks. For the jointed rock mass tunnel, the cohesion and internal friction angle of the surrounding rocks are improved as 1.7 times and 1.2 times of the initial value, which can simulate the reinforcement effect of rock bolts. Comparing with analytical results, the improved internal friction angle is nearly consistent with analytical result. The reinforcement effect of rock bolts is simulated obviously when the mechanical parameters of surrounding rocks are increased simultaneously. The engineering application shows that the equivalent anchoring method can reasonably simulate the effect of rock bolts, which can provide reference for stability analysis of three-dimensional tunnel simulations.